Clarification on the choice of sheet positioning in friction stir welding of dissimilar materials. (April 2020) - Kesharwani, Rahul; Imam, Murshid; Sarkar, Chiranjit
Graphical abstract: Abstract: The material mixing in FSW of the dissimilar weld is significantly affected by the local heat partitioning arising from the difference in mechanical and thermal properties at the interface of the tool/soft/hard materials. Based on the experimental observations made from cross-flow weld configurations, it is proposed that pure Cu should be placed on the retreating and 6061-T6 AA on the advancing sides for obtaining the defect-free weld in dissimilar butt welding. For the successful weld obtained based on the suggested sheet positioning, the ultimate tensile strength (UTS) and percentage uniform elongation are 252 MPa and 12.2%, respectively.